Domestic Violence, Companion Animal Abuse, and Help-Seeking: The Mediating Role of Fear of Lethal Violence - Barrett, Betty Jo (Women & criminal justice, 2022)
This study assesses the relationship between threatened/enacted violence against companion animals, intimate partner violence (IPV), fear of lethal violence, and help-seeking in a community sample of IPV survivors in Canada (n = 630). After controlling for socio-demographic covariates, IPV survivors who report animal maltreatment by their partner were significantly more likely to fear for their lives and to seek help from multiple sources of support than survivors who did not report animal maltreatment, with the relationship between animal abuse and help-seeking mediated by survivors’ fear of lethal IPV. Implications for the provision of effective services and supports to this high-risk population of IPV survivors are discussed.